The Effectiveness of Zakat Institutions Empowerment Using the Zakat Village Index: Analysis in Sumenep East Java - Ach yasin (ITB AAS INDONESIA Surakarta, 2022)
This study examines zakat-based village empowerment. This research was conducted as a response to the less than optimal program of zakat institutions and at the same time as an alternative in empowering by focusing on the feasibility of villages as measured through the Zakat Village Index (IDZ). Eligibility is based on the economic dimension, the health dimension, the education dimension, the social and humanitarian dimension and the da'wah dimension. From these 5 (five) dimensions, the Zakat Village Index will be produced. This study uses a mixed method research method. The objects in this study are several villages in Sumenep Regency, which have received empowerment assistance and which have not received empowerment assistance from zakat institutions. The results in this study indicate that from calculating the village zakat index (IDZ) in Sumenep Regency. Of the 11 (eleven) villages that became the object of research, there are 3 (three) villages that believe Gadding Village with an IDZ index of 0.39, Gunung Kembar Village with an IDZ index of 0.39, Jebe'en Village which should be a priority in empowerment by zakat institutions. By considering the IDZ score, it is hoped that empowerment will be better and more effective